If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + -6u + 3 + -4u + 9p + 14 = 0 Reorder the terms: 3 + 14 + p + 9p + -6u + -4u = 0 Combine like terms: 3 + 14 = 17 17 + p + 9p + -6u + -4u = 0 Combine like terms: p + 9p = 10p 17 + 10p + -6u + -4u = 0 Combine like terms: -6u + -4u = -10u 17 + 10p + -10u = 0 Solving 17 + 10p + -10u = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + 10p + -17 + -10u = 0 + -17 Reorder the terms: 17 + -17 + 10p + -10u = 0 + -17 Combine like terms: 17 + -17 = 0 0 + 10p + -10u = 0 + -17 10p + -10u = 0 + -17 Combine like terms: 0 + -17 = -17 10p + -10u = -17 Add '10u' to each side of the equation. 10p + -10u + 10u = -17 + 10u Combine like terms: -10u + 10u = 0 10p + 0 = -17 + 10u 10p = -17 + 10u Divide each side by '10'. p = -1.7 + u Simplifying p = -1.7 + u
| -0.15x^2+150x=11000 | | -2=3+5x | | -0.15x^2+150x= | | x(x+4)=-20 | | 10(-0.2)+4=2(2) | | 3u+2u=25 | | 2(42x+2y)x(52x+3y)-(33x+6y)= | | 10(-0.4)+4=2(2) | | 21+7g=98 | | 15n^2+3n=0 | | -3(k-12)=48 | | 5x+12+6x-10=120 | | 10(-2.5)+4=2(2) | | 7x+3+72=180 | | 3+5+x-3=6+8-3+1 | | 63=12+b | | Cos^2(x)-3cosx+2=0 | | 3+w=5+7w | | 1=-8+3b | | 2(5x+5)=9x+8 | | 8x-5=93 | | 360=230+67+x | | -2(-1y+-5)=8 | | -2+6(1-7k)=24 | | Y-1=x-6 | | x+9f+10=5jforx | | (3x^2-5x+7)+(4x^2+9x-1)= | | 13+6x-5=4x+8 | | 3h-(-8)=14 | | 2x+-1=1 | | 10x=8x+8 | | -22=7(8f-5) |